Juridical interferences in patient’s autonomy: the uncertain frontiers of law - Diaz Pintos, Guillermo (Medicina e Morale, 1995)
The artide introduces a vision of moral autonomy other than that of individualistic liberalism, upon which the value of consent can be adequately founded, in relation with interferences of third parties in the individual's freedom of action, as well as establishing its "practical" limits. In order to do so, the author starts by expounding the liberai doctrine of moral autonomy and the justifications it uses to legitimate third parties' interventions in individual freedom, which are a series of theories about consent or prosecution and achievement of the "life plans" of the intervened subject, whose knowledge is presupposed or can be obtained in various ways. The criticism focuses on two elements: the existing difficulties in distinguishing self-regarding acts from those which are otherregarding; and the impossibility of distinguishing between actions and omissions as the origin of the relevant damage that can be derived from such interventions, both of which are theoretical suppositions that constitute the notion which is being questioned. As a possible solution to these weaknesses, this article suggests a substantive notion of autonomy based on an adequate analysis of consent, understood in terms of the notion of representation, instead of understanding it as an authorization or permission to act an account of an other person, which are two formai notions rather frequent in the liberalist approach. Finally, the author shows the reflection of the preceding theoretical supposition in a sentence of the Spanish Constitutional Court of 1990, which analyses the scope of the limitations of the fundamental rights of the prisoners who go on hunger famine strike. This leads to reaffirming the idea supported and to the conclusion of the analysis.